“As an Englishwoman, As a Writer”: The Edinburgh and Quarterly Reviews, Early Nineteenth-Century Authorship, and the Reception of Frances Burney’s The Wanderer - Cove, Patricia (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2014)
The reception of Frances Burney’s final novel, The Wanderer, demonstrates the periodical press’s ability to shape British concepts of authorship and audience expectations in the Romantic era. William Hazlitt’s and John Wilson Croker’s reviews of this novel illustrate that, despite their apparent ideological differences, the Edinburgh and Quarterly reviews could combine to redefine the British literary tradition and reading public in national and masculinist terms. Such reviews attempt to police the borders of the British canon, to the exclusion of writers like Burney who seem not to meet the new demands of Romantic-era review culture.